Control for cooperative transport of a bar-shaped payload with rotorcraft UAVs including a landing stage on mobile robots. Issue 16 (9th December 2020) - Gimenez, Javier; Salinas, Lucio R.; Gandolfo, Daniel C.; Rosales, Claudio D.; Carelli, Ricardo
Abstract : This paper considers the cooperative transport problem of a cable-suspended rigid bar with two rotorcraft UAVs considering collision avoidance, weight distribution, and wind perturbations. The proposal is based on null-space theory and includes a landing stage where the load is settled down on a formation of ground robots. Therefore, a variable formation is considered according to the task phase. In order to simulate the proposal in a realistic environment, very complete dynamic models for UAVs, ground robots, and load are considered. An adaptation stage is incorporated to link the control actions with the inputs required by the dynamic models. Theoretical bounds for the errors are studied under the assumption that perfect velocity tracking is not fulfilled.